Constitutive activation of integrin αvβ3 contributes to anoikis resistance of ovarian cancer cells. Issue 2 (1st December 2020) - Dolinschek, Romana; Hingerl, Julia; Benge, Anke; Zafiu, Christian; Schüren, Elisabeth; Ehmoser, Eva‐Kathrin; Lössner, Daniela; Reuning, Ute
Abstract : Epithelial ovarian cancer involves the shedding of single tumor cells or spheroids from the primary tumor into ascites, followed by their survival, and transit to the sites of metastatic colonization within the peritoneal cavity. During their flotation, anchorage‐dependent epithelial‐type tumor cells gain anoikis resistance, implicating integrins, including αvß3. In this study, we explored anoikis escape, cisplatin resistance, and prosurvival signaling as a function of the αvß3 transmembrane conformational activation state in cells suspended in ascites. A high‐affinity and constitutively signaling‐competent αvß3 variant, which harbored unclasped transmembrane domains, was found to confer delayed anoikis onset, enhanced cisplatin resistance, and reduced cell proliferation in ascites or 3D‐hydrogels, involving p27 kip upregulation. Moreover, it promoted EGF‐R expression and activation, prosurvival signaling, implicating FAK, src, and PKB/Akt. This led to the induction of the anti‐apoptotic factors Bcl‐2 and survivin suppressing caspase activation, compared to a signaling‐incapable αvß3 variant displaying firmly associated transmembrane domains. Dissecting the mechanistic players for αvß3‐dependent survival and peritoneal metastasis of ascitic ovarian cancer spheroids is of paramount importance to target their anchorage independence by reversing anoikis resistance and blocking αvß3‐triggered prosurvival signaling. Abstract : EOC cells are shed from the primary tumor and survive the transit in ascites to colonize at metastatic sites. In EOC cell transfectants, a constitutively active αvß3 with unclasped TMD conferred anoikis resistance via prosurvival signaling implicating the activation of the EGF‐R, FAK, src, PKB/Akt, and Erk, compared with rapid onset of apoptosis by a signaling‐incompetent αvß3 with associated TMD.